2014
DOI: 10.1073/pnas.1408888111
|View full text |Cite
|
Sign up to set email alerts
|

Native microbiome impedes vertical transmission of Wolbachia in Anopheles mosquitoes

Abstract: Significance Factors influencing Wolbachia transfer into new species remain poorly understood. This is important as Wolbachia can influence speciation and is being developed as a novel arthropod-borne disease control approach. We show the native microbiota of Anopheles impede vertical transmission of Wolbachia . Antibiotic microbiome perturbation enables Wolbachia trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
225
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(247 citation statements)
references
References 63 publications
18
225
3
1
Order By: Relevance
“…Moreover, Caccia et al reported that mortality of the cotton leafworm Spodoptera littoralis was increased by the gut bacteria Serratia and Clostridia species invading the body cavity through toxin-induced epithelial lesions (31). In Anopheles, the symbiotic bacterium Asaia is responsible for inhibiting Wolbachia transmission but antibiotic microbiome perturbation enables Wolbachia transmission (34). Examples of the contributory role of gut microbiota to invading intestinal pathogens are also found among vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Caccia et al reported that mortality of the cotton leafworm Spodoptera littoralis was increased by the gut bacteria Serratia and Clostridia species invading the body cavity through toxin-induced epithelial lesions (31). In Anopheles, the symbiotic bacterium Asaia is responsible for inhibiting Wolbachia transmission but antibiotic microbiome perturbation enables Wolbachia transmission (34). Examples of the contributory role of gut microbiota to invading intestinal pathogens are also found among vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, while studies on the application of microbes such as Wolbachia to control human disease have advanced, we still lack basic insight into the natural microbial communities associated with vectors, from viruses to bacteria to single‐celled eukaryotes. Given that infectious vector‐borne diseases are increasing in humans (Jones et al., 2008), our goal is to characterize the composition and structure of microbiota in mosquito vectors across landscapes altered by human activities, where differences may influence the biology of vectors, their vectorial capacity, and ultimately the outcome of microbe‐mediated disease control (Hughes et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Further, the microbiomes of arthropod vectors of human pathogens can affect the transmission of zoonotic pathogens (Weiss and Aksoy, 2011;Hughes et al, 2014;Narasimhan et al, 2014). Laboratory experiments have found that higher tick microbiome diversity is negatively correlated with colonization success of the Lyme disease pathogen, Borrelia burgdorferi (Narasimhan et al, 2014).…”
mentioning
confidence: 99%